Modeling of a polyimide diaphragm for an optical pulse pressure sensor - Hasikin, K.; Soin, N.; Ibrahim, F. (2009)
This paper presents the modeling of a polyimide diaphragm for an optical pulse pressure sensor. Polyimide is a type of polymer materials that possessed low linear coefficient of thermal expansion and has good thermal stability. The polyimide diaphragm has been designed and its performance is analyzed in terms of diaphragm deflection, diaphragm pressure sensitivity and diaphragm resonance frequency. Two design parameters namely diaphragm radius and diaphragm thickness are varied to study the diaphragm performance. It can be concluded that the modeled micro-diaphragm with a diaphragm radius of 90Î¼m and diaphragm thickness of 4Î¼m respectively has satisfied the maximum allowable deflection and operated in optimum frequency response.